A Description of Self Stigma Incidence in Post COVID-19 Patients in Kaliwates District Jember Regency - Sekar Ayu Widowati; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan; Jon Hafan Sutawardana; Yeni Fitria (KHD-Production, 2022)
The condition of the COVID-19 pandemic resulted in the emergence of feelings of anxiety, distress, and stress. One of the impacts of COVID-19 on mental health is the emergence of self-stigma in patients who have recovered from COVID-19. Self-stigma can give rise to negative attitudes in themselves over their condition. This study is aimed to describe the self-stigma incidence in post-COVID-19 patients in Kaliwates Subdistrict. This research design was descriptive quantitative with 86 post-COVID-19 patient respondents domiciled in Kaliwates Subdistrict determined by purposive sampling technique. Data collection was conducted by the Self Stigma Scale (SSS) questionnaire. The results showed that the median value of self-stigma was 30.50 with a minimum value of 0 and a maximum value of 56. A total of 14 people had a total score of 0 which means that 14 respondents (16%) did not experience self-stigma, while 72 others (84%) felt the existence of self-stigma with a different total score. This research is important to detect self-stigma to support the recovery process of post- COVID-19 patients. Nurses are expected to be able to carry out the further follow-up, act as counselors and provide interventions such as cognitive therapy for post-covid-19 patients who experience self-stigma.